(untitled) (Research, Society and Development, 2021)
In recent decades, the fruit trade in Brazil has grown significantly, serving the domestic and foreign markets. Among the main fruits produced and traded, mango, the most exported fruit in Brazil, stands out. In this work we analyzed the time series of returns and volatility of weekly prices of two mango varieties, Palmer and Tommy Atkins produced in the São Francisco Valley, the region with the highest mango production in the country. The methods Detrended fluctuation analysis (DFA) and Detrended cross correlation analysis (DCCA) were used to calculate scaling exponents of autocorrelations and cross correlations between the analyzed series. The results showed that the volatility series have stronger persistence than the return series that presented two regimes of scale invariance with anti-persistent correlations on the larger temporal scales. Cross-correlations between the series of returns also show two scaling regimes with exponents similar to the series of returns of the Tommy variety. The values ​​of the correlation coefficient obtained by the Detrended cross correlation coefficient method showed that for both returns and volatility the correlations between the series are positive, increase with time scale and are stronger for the series of returns.